Ganda xylophone music: another approach - Cooke, Peter (African Music : Journal of the International Library of African Music, 1970)
Over a period of many years musicologists have interested themselves in the Akadinda and Amadinda techniques of the Ganda people and a growing number of published articles give mention of, or are devoted to these two instruments. In a sense, the aims of this paper are similar to those stated by Kubik, namely "to show by what factors the individual parts of Kiganda xylophone music are predetermined and to what extent they are interdependent”. My approach, however, will be to compare the internal structure of the xylophone parts with known song texts which are related to them. I hope to demonstrate that the instrumental structures are closely related to the musico-phonological structures of the songs. I believe that such a relationship will be found inherent to all tuned instrument styles in Ganda culture and hope that this paper will contribute further to our understanding of this rich field of musical activity.